BLENDED LEARNING IN EFL: COMBINING TRADITIONAL CLASSROOM INSTRUCTION WITH DIGITAL INNOVATION (SCIENCE TIME JOURNAL, 2026)
The growing integration of digital technologies in education has led to the emergence of blended learning as a prominent instructional approach, particularly in English as a Foreign Language (EFL) contexts. Blended learning combin s traditional face-to-face classroom instruction with digital and online learning components, aiming to enhance learner engagement, autonomy, and languageproficiency. This study investigates the effectiveness of blended learning in EFL by examining its impact on student engagement, language skill development, and learning outcomes in higher education. A mixedmethods research design was employed, involving questionnaires, classroom observations, and instructor interviews. The findings reveal that blended learning significantly improves student motivation, interaction, and overall language competence compared to purely traditional instruction. However,successful implementation depends on teacher preparedness, institutional support, and balanced pedagogical design. The study concludes that blended learning offers an effective and sustainable model for EFL instruction when appropriately integrated.